Upaya Membangun Kesadaran Masyarakat dan Deteksi Dini terhadap Penyakit Tidak Menular di Kelurahan Simomulyo Baru, Kota Surabaya - Faradila, Putri Anisah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Non-communicable diseases (NCDs), such as hypertension, diabetes, and obesity have become major health issues in Indonesia, with their prevalence continuously increasing, particularly in urban areas. This study aims to describe the implementation of the NAGA SAKTI Program in raising public awareness about NCDs. The method used is a community-based approach that involves blood pressure measurement, random blood glucose (RBG) test, and Body Mass Index (BMI) assessment, followed by education through leaflets and discussions. The program results show that the majority of participants are at risk for hypertension (50% pre-hypertension), and 6.8% show high blood glucose levels, indicating a risk of diabetes. Group exercise and health education have proven effective in increasing public understanding of the importance of early detection of NCDs. This program also successfully raised awareness of healthy lifestyles within the community. It is expected that the NAGA SAKTI Program can be used as a model for sustainable community service and can be implemented in other urban areas to reduce the prevalence of NCDs.